2016
DOI: 10.1063/1.4950999
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of continuous-flow separation of viable/nonviable yeast cells using a nonuniform alternating current electric field with complex spatial distribution

Abstract: The variability in cell response to AC electric fields is selective enough to separate not only the cell types but also the activation states of similar cells. In this work, we use dielectrophoresis (DEP), which exploits the differences in the dielectric properties of cells, to separate nonviable and viable cells. A parallel-plate DEP device consisting of a bottom face with an array of micro-fabricated interdigitated electrodes and a top face with a plane electrode was proposed to facilitate the separation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Finally, by employing a top-bottom microelectrode apparatus, microspheres are detectable both above and below the barcoded particle. While the fabrication of top and bottom electrodes for microfluidic applications are infrequent, recent studies have found effective means to produce results using glass-embedded electrodes sandwiching PDMS-based channels, and we believe such methods are possible for in vitro design experiments 49 . Furthermore, our top-bottom electrode configuration is independent of vertical alignment between electrodes as both systems emit/detect their own electric field areas, reducing the burden of micron-scale alignment protocols and promoting simpler microfluidic manufacturing.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, by employing a top-bottom microelectrode apparatus, microspheres are detectable both above and below the barcoded particle. While the fabrication of top and bottom electrodes for microfluidic applications are infrequent, recent studies have found effective means to produce results using glass-embedded electrodes sandwiching PDMS-based channels, and we believe such methods are possible for in vitro design experiments 49 . Furthermore, our top-bottom electrode configuration is independent of vertical alignment between electrodes as both systems emit/detect their own electric field areas, reducing the burden of micron-scale alignment protocols and promoting simpler microfluidic manufacturing.…”
Section: Discussionmentioning
confidence: 99%
“…A shorter electrode substrate was used to investigate the dielectrophoretic behavior of cells and to explore the optimal operation condition and the optimal length of the flow chamber for a high throughput cell separation, while the longer one was used for the quantitative evaluation of the separation performance of the proposed device. The length of the shorter electrode substrate was determined by taking into account the results of the yeast-cell separation; 16 the length of the electrode longer than the previously used one was found to be necessary for mammalian cells. The shorter interdigitated electrodes were fabricated in a similar manner by standard photolithography.…”
Section: A Cell Preparationmentioning
confidence: 99%
“…We used a three-dimensional (3D) nonuniform AC electric field established in the whole volume of a parallel-plate type flow chamber to enhance the process of cell separation. 15,16 In general, the ideal DEP cell-separation device aimed at clinical applications would take the best advantage of the field gradient established in the flow chamber to manipulate cells without damaging them by joule heating or high voltage. In the proposed method, the electric field creates sites of minimum field gradient in the middle of the flow stream slightly above the bottom face of the flow chamber, while simultaneously creating sites of the maximum field gradient on the edges of the interdigitated electrode arrays at the bottom face.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations